Turning to friends in preference to parents for support in early adolescence: does this contribute to the gender difference in depressive symptoms? - Wright, Nicky; Sharp, Helen; Gay, Jessica; Pickles, Andrew; Hill, Jonathan (Frontiers in Child and Adolescent Psychiatry, 2023)
Introduction Based on established evidence for gender differences in friendship patterns, and on vulnerability associated with early reliance on friends, we hypothesised that in 13 year olds, preferentially turning to friends over parents for emotional support contributes to the gender difference in depressive symptoms. Method Using a cross-sectional design, 671 adolescents (mean age 13.11 years [SD = .52], 53.7% girls) in a UK birth cohort (Wirral Child Health & Development Study; WCHADS) reported on turning to their parents and to their friends when distressed (Network of Relationships Inventory; NRI) and their depressive symptoms (Short Mood & Feelings Questionnaire, SMFQ). Preferential turning to friends was assessed as turning to friends minus turning to parents for support. Analyses used path analysis using the gsem command in Stata. Results Girls had higher depressive symptoms than boys (p < .001). Consistent with hypotheses, girls had higher scores than boys for preferential turning to friends (p < .001). Preferential turning to friends was associated with higher depressive symptoms (p < .001) and this mediated the gender difference in depressive symptoms (p < .001). The association between preferential turning to friends and depressive symptoms was stronger in girls than in boys (p = .004). Conclusions In young adolescents, preferential turning to friends over parents when distressed, and the association between preferential turning and depressive symptoms, are markedly higher in girls than in boys. This reflects either a gender difference in social vulnerability to depression, or a greater impact of depression on reliance on friends instead of parents in girls. While clarifying the directions of influence requires prospective study, these findings provide the first evidence that the assessment of young adolescent depression should attend to the degree of reliance on friends as well as on parents.